Pemberdayaan UMKM melalui Inovasi Keripik Daun Singkong dan Pemasaran Digital di Dusun Dermojurang - Alifiawan, Muhammad Akmal Arkan; Toloa, Sakinah; Chania, Nesha Putri; Ananda, Rosa Amalia; Asidqiyah, Rifki; Nurcahya, Selvia; Irianto, Daffa Ulhaq; Ramadana, Galang Nifan; Octaviandi, Reyfaldi Aulia; Ramadhan, Aji Krisna; Diwanti, Dyah Pikanthi (Prosiding Seminar Nasional Program Pengabdian Masyarakat, 2025)
This MSME empowerment program aims to enhance product innovation and increase knowledge of digital marketing to business actors in Dermojurang. One of the proposed innovations is the production of cassava leaf chips as an alternative product with economic potential. The methods that used in this activity were digital marketing socialization, trial production practice, and e-commerce account creation training to help MSMEs expand their marketing reach. Socialization covered an understanding of MSME digitalization, digital marketing strategies, and packaging references to increase product appeal. In addition, logo and packaging sticker designs were also created as product branding examples to make them more professional. The cassava leaf chip production practice was conducted to teach proper processing techniques and identify product development potential. The results of this activity showed that participants experienced an increase in understanding of digital marketing and product innovation. Of the 12 participants, only 25% initially understood the concept of digital marketing, but after the training, this number increased to 83%. The main challenges still faced include limited access to technology and experience in managing digital platforms. With proper guidance, MSMEs can be better prepared to compete in the market and utilize technology to enhance their product competitiveness. Therefore, continued support from various stakeholders is essential to ensure the sustainability of this program